Landlords' rights and duties in Florida - Warda, Mark (Sphinx legal., 2005)
Understanding your rights and responsibilities under Florida landlord/tenant law is essential to becoming a successful and profitable landlord in the state of Florida. A basic knowledge of the Florida law can help avoid becoming liable to tenants for damages and attorney's fees. Landlords' Right & Duties in Florida discusses issues including dealing with problems during a tenancy, protecting yourself from liability for injuries and crimes, and evicting a tenant. This guide provides east-to-understand explanations of landlord/tenant law, as well as blank forms, flow charts, and examples from actual cases. Using this book can help save you money and avoid potential liabilities.-Screening Prospective Tenants -Protecting Yourself from Liabilities -Evicting a Tenant -Changing the Terms of a Tenancy -Making a Claim for Damages -Terminating a Tenancy, Early Ready-to-Use Forms with Instructions: Apartment Lease Rental Agreement Notice of Termination Back Check Notice Eviction Summons and many more ...-Florida statutes -Eviction flowcharts -Step-by-step instructions -Ready-to-use, blank forms.